Investigating First and Second Language Speaker Intuitions of Phrasal Frequency and Association Strength of Multiword Sequences. Issue 1 (18th October 2022) - Yi, Wei; Man, Kaiwen; Maie, Ryo
Abstract: In this study, we investigated the accuracy of first language (L1) and second language (L2) speakers' intuitive judgments of phrasal frequency and collocation strength, and examined the linguistic influences that give rise to these judgments. L1 and L2 speakers of English judged 180 adjective–noun collocations as (a) high frequency, medium frequency, or low frequency and (b) high association, medium association, or low association. Results showed that neither L1 nor L2 speakers demonstrated accurate intuitive judgments of phrasal frequency and association strength. Both groups of participants employed linguistic information at phrase and single‐word levels when giving intuitive statistical estimates. We found judgments of phrasal frequency and association strength to be intertwined for both L1 and L2 speakers. Taken together, these findings shed new insight on understanding language users' statistical knowledge of multiword sequences. Abstract : A one‐page Accessible Summary of this article in non‐technical language is freely available in the Supporting Information online and at https://oasis‐database.org